The Psychometric Properties of the Norwegian version of The Child and Adolescent Trauma Screen (CATS) - Borren, Ingrid; Kaiser, Sabine (PsykTestBarn, 2021)
Description: The Child and Adolescent Trauma Screen (CATS) is a screening instrument developed for children aged 7–17 and provides preliminary prognostic information about posttraumatic stress. CATS consists of two parts: part 1 maps traumatic events, and part 2 measures symptoms of posttraumatic stress. Part 2 is divided into four symptom categories adjusted in accordance with the diagnostic changes of the DSM-5 trauma diagnosis. CATS was developed and validated by Sachser et al. (2017). The Norwegian Centre for Violence and Traumatic Stress Studies (NKVTS) was involved in the development of the scale and responsible for the Norwegian translation. Literature search: The literature search resulted in the following documentation: one published Norwegian article, and one Swedish master’s thesis, both reporting relevant psychometric information for CATS. Psychometrics: The results indicate sufficient internal consistency for the four scales. Sufficient test-retest reliability for the total score was also detected in the Swedish sample. A confirmatory factor analysis was conducted for a mixed sample of children from Norway, Germany and the US, and the underlying DSM-5 factor structure for posttraumatic stress disorder was confirmed. There was also evidence for convergent and construct validity. The Swedish norms are, however, limited in terms of age and geography, and Norwegian norms for the instrument are lacking. Conclusion: There is insufficient documentation to firmly conclude on the psychometric properties of CATS. More studies, particularly norm data, are needed from Scandinavian populations. The scale must therefore be used with caution in Norway.